Personification Physiology in Pedagogy: Transformation of Teachers as Living Model 11 System Body Towards Holistic Education at SDIP Baitul Maal - Maya Yunus (Global Education Journal, 2025)
Study This motivated by the phenomenon dichotomy between mastery material biology in a way theoretical with practice style life healthy teachers at school basis, which causes low effectiveness education character based exemplary behavior. Problems main rooted in low literacy health teacher functionalities that impact disconnection the value of “keeping “trust body “in” curriculum holistic research​ This aims for design and analyze implementation mastery of 11 systems body humans by teachers as an educational model holistic at SDIP Baitul Maal. Use method qualitative with design studies case intrinsic, data collected through triangulation techniques that involve observation participatory, interview in-depth, and study documentation against 11 selected teachers in a way purposive. Research results show existence improvement literacy physiological teacher​ significant from average score of 61 to 88, which triggered teacher transformation as Living Model through synchronization regulations emotion-based neuroscience and management energy metabolic findings​ main disclose that integration analogy physiological in eye non- science and policy subject’s ecosystem school Healthy capable lower-level anxiety student by 40% and reduce number absence medical up to 25%. Research This recommend standardization curriculum “Literacy “training Physiological-Pedagogical “for educator as condition absolute for realize resilience schools and education sustainable holistic.​